Sistem Pemerintahan Dalam Islam Perspektif Sayyid Qutb - Jatim, Jatim (International Conference on Islamic Studies, 2020)
Islam is a religion that views the importance of government in order to bring about justice in various fields. Government in the view of Islam, functions to control the proceedings of justice in society. Thus, this article attempts to discuss the government system in the perspective of Sayed Qutb, using qualitative methods, which are presented in a descriptive analysis. Through this method, the author concludes that the system of government in Islam according to Sayed Qutb is built on the basis of freedom of the soul, equality of human rights and social security.